Epoxy/α‐alumina nanocomposite with decreased dielectric constant and dielectric loss. Issue 7 (29th September 2016) - Chen, Yun; Zhang, Donghai; Wu, Xiaofeng; Wang, Haosheng; Xue, Yang; Wu, Ruiwen; Zhang, Zhong; Chen, Yunfa
Abstract : In this work, the dielectric spectroscopy and dynamic mechanical thermal spectroscopy of neat epoxy and epoxy nanocomposites modified by boehmite, γ‐alumina and α‐alumina nanoparticles, respectively, were investigated. The dielectric behavior of epoxy resin was significantly affected by the incorporation of α‐alumina nanofiller. The values of real and imaginary part of relative permittivity of epoxy/α‐alumina nanocomposite were even lower than these of neat epoxy. On the contrary, these values of boehmite and γ‐alumina nanocomposites were higher than these of neat epoxy. The glass transition temperature ( T g ) determined by dynamic mechanical thermal analysis (DMA) was obviously decreased when boehmite nanofiller was added into the epoxy nanocomposite. The value of T g was slightly decreased by γ‐alumina and apparently increased by α‐alumina nanofiller. These changes of performance may be attributed to that the existence of α‐alumina nanoparticles restricted the mobility of polymer molecular chains. POLYM. COMPOS., 39:2307–2319, 2018. © 2016 Society of Plastics Engineers